Genistein and Selected Phytoestrogen-Containing Extracts Differently Modulate Antioxidant Properties and Cell Differentiation: an in Vitro Study in NIH-3T3, HaCaT and MCF-7 Cells - Šušaníková, I; Puchl'ová, M; Lachová, V; Švajdlenka, E; Mučaji, P; Smetana, K; Gál, P (Folia biologica, 2019)
During the last decades, plant extracts containing phytoestrogens have increasingly been used as an alternative to oestradiol hormone replacement therapy. The aim of the present study was to compare the effects of genistein with those of different phytoestrogen-containing plant extracts (from red clover flowers and soybeans) on the proliferation and differentiation of NIH-3T3, HaCaT and MCF-7 cells. Our results showed poor correlations between direct anti/pro-oxidant effects and cytotoxicity of the tested samples. In contrast, genistein showed a direct correlation between significant pro-oxidative effects at cytotoxic concentrations and almost no pro-oxidative effects at non-cytotoxic concentrations. Moreover, the tested red clover extract and genistein induced keratin-8 (luminal and prognostic marker in breast cancer) expression only in MCF-7 cells, but this effect was not seen following treatment with the soybean extract. From this point of view, the effect of consumption of phytoestrogens in oestrogen-positive breast cancer remains to be elucidated. In conclusion, our study demonstrates that various phytoestrogen- containing plant extracts and genistein are able to specifically modulate antioxidant properties and differentiation of studied cells.
Keywords: lidé; Cell Proliferation; NIH 3T3 Cells; MCF-7 Cells; fytoestrogeny; myši; Humans; rostlinné extrakty; Mice; antioxidancia; MFC-7 buňky; buněčná diferenciace; proliferace buněk; buňky NIH 3T3; Keratin-8; zvířata; keratin-8; genistein; Animals; Genistein; Plant Extracts; Cell Differentiation; Antioxidants; Phytoestrogens